Post-hajj acute respiratory infections: Proportion and associated factors pilgrims from an Indonesian hajj guidance group - Devita, Ninda; Rachmawaty, Farida Juliantina; Andriyanto, Eko; Muhammad, Afivudien (Faculty of Medicine, Universitas Islam Indonesia, 2026)
Background: The Hajj pilgrimage is the largest mass gathering, posing a high risk of acute respiratory infection (ARI) transmission. Post-Hajj ARI represents a major public health concern, as returning pilgrims may serve as carriers and potentially transmit pathogens to their home communities. Identifying the proportion and risk factors of post-Hajj ARI is essential for developing effective preventive strategies.Objectives: This study aimed to determine the proportion of post-Hajj ARI and associated risk factors among pilgrims from KBIHU (Indonesian hajj and umrah guidance group) Multazam Ad-Dakwah Yogyakarta 2025.Methods: This cross-sectional study used an online questionnaire. Respondents were pilgrims from KBIHU Multazam Ad-Dakwah Yogyakarta who experienced ARI symptoms after the 2025 Hajj. Sociodemographic characteristics, vaccination history, preventive behaviors, and metabolic risk factors were collected. Data were analyzed using multivariate logistic regression. Odd ratios with 95% CIs were calculated. P-values <0.05 were considered statistically significant.Result: In total, 112 pilgrims were included. Of these, 20.5% were aged 60 years or older. More than half (57.1%) reported comorbidities, mainly hypertension and dyslipidemia. Most participants were non-smokers (82.1%). They reported moderate adherence to preventive behaviors, including mask use (54.5%) and hand hygiene (56.3%). Meningococcal vaccination coverage was universal. Coverage for influenza (75.0%), COVID-19 (46.4%), and pneumococcal vaccination (6.3%) was lower. Overall, 100 pilgrims (89.3%) experienced ARI symptoms. Bivariate analysis showed that age over 60 years was significantly associated with ARI (cOR 4.697; 95%CI: 1.206–18.295; p=0.026). Multivariate logistic regression confirmed that older age was the only significant determinant of ARI (aOR 4.88; 95% CI: 1.22–19.53; p=0.02).Conclusion: Age 60 or over is a significant risk factor for post-Hajj ARI. Focused preventive strategies targeting elderly pilgrims are essential to reduce ARI-related morbidity and mortality after the Hajj.